IMPLEMENTASI KEBIJAKAN PELAYANAN IZIN MENDIRIKAN BANGUNAN (IMB) DI KANTOR DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU KABUPATEN SIGI - Nasaruddin Nasaruddin (Katalogis, 2018)
This study aims to identify and describe Implementation of Building Service Permit Policy (IMB) at the Office of Investment and Service Integrated One Door DPM-PTSP Sigi District. The author uses the theory of George C. Edward III which includes factors Communications, Resources, Disposition, and Bureaucratic Structure. The type of research is using qualitative descriptive methodology. Based on the acquisition shows that the implementation of government policy in licensing service especially the building permit service (IMB) in Sigi Regency has not fully run well and has not had a positive impact on development. This is evidenced from the four aspects studied, has not supported the factors proposed by Edward III is related to communication factors, resource factors and disposition factors. Can be explained that not maximally Implementation of Government Policy in licensing service specially Permit to construct building in Sub-Province of Sigi which impact on execution of comprehensive development in Sigi Regency. This can be seen from the number of people taking care of the IMB is very less. Only bureaucratic structural factors are eligible to implement the policy but also have not shown significant positive impacts so that the priority of development success programs has not been achieved, including giving serious attention to the success of policy implementation especially in terms of licensing service in Sigi Regency.